2021
DOI: 10.21037/apm-21-1296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic efficacy of three methods to prevent re-adhesion after hysteroscopic intrauterine adhesion separation: a parallel, randomized and single-center trial

Abstract: Background: This research aims to study the efficacy of an integrated approach to prevent and treat the recurrence of intrauterine adhesions (IUA) after hysteroscopic adhesiolysis.Methods: A total of 96 patients diagnosed with moderate-to-severe intrauterine adhesions (IUA) in Nantong Maternal and Child Health Hospital from January 2016 to December 2019 were included in this parallel, randomized and single-center trial. Moderate (48 cases) and severe (48 cases) patients were randomly divided into three groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…A study found that AFS score has predictive value for post-operative live birth in patients with IUA ( Cao et al, 2021 ). For patients with moderate adhesion, the lower the AFS score, the higher the post-operative pregnancy rate ( Zhang et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…A study found that AFS score has predictive value for post-operative live birth in patients with IUA ( Cao et al, 2021 ). For patients with moderate adhesion, the lower the AFS score, the higher the post-operative pregnancy rate ( Zhang et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials(RCT) found that for patients who placed IUD after TCRA, the overall conception rate and live birth rate were 27.5%-47.2% and 20.0%-28.0%, respectively [4,8,9], the reformation rate was 35.0%-43.1% [9,10]. It was reported that 62.7% of IUA patients returned to normal menstruation by this way [1].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of Asherman syndrome aims to restore the anatomy and volume of uterine cavity, in the meantime, improves symptoms of different clinical presentations, and most importantly, to prevent the reformation of IUA and repair endometrium. Transcervical resection of adhesion(TCRA) by hysteroscopy is the routine operation for IUA, however, studies showed that the recurrent rate after TCRA reach up to 48.0%-62.5%, and the pregnancy rate is only 22.5%-33.3% [3,4]. Therefore, taking measures to prevent readhesion and promote endometrial regeneration and repair endometrium is absolutely crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of 9 mg/diet estrogen before TCRA and 10 mg/ diet after TCRA improved pregnancy rates and menstrual cycles in patients with moderate or severe IUA (Liu AZ et al, 2016); however, estrogen therapy may increase the risk of cancer (Rossouw et al, 2002) and venous thrombosis (Bracamonte and Miller, 2001). Balloon dilatation after TCRA and early second-look hysteroscopy improved pregnancy outcomes (Sun et al, 2020), and the appropriate delay of balloon placement in the uterine cavity prevented re-adhesion but was not effective in severe IUA (Zhang et al, 2021a). The dilated balloon is a nonvariable sphere that is not able to be plasticized according to the shape of the uterine cavity, resulting in ineffective improvement of adhesions in the uterine horns (Sun et al, 2020).…”
Section: Intrauterine Adhesionmentioning
confidence: 99%